Challenges in Methodological Issues in Feminist Criticism and Feminist Literary Criticism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores feminist literary criticism and the emergence of global feminist literary criticism within the overlap of literary theory and feminist and gender studies. It further conveys the extensive nature of feminist literary criticism, showcasing its variations and uses across various social and cultural settings, merging the feminist perspective with racial and cultural contexts. Feminist Criticism has faced, and continues to face, challenges that hinder its ability to connect with all women globally, resulting in a gap that has gradually expanded over time and alienated women from their actual rights. This consider offers a brief outline of the history of Western women's activist scholarly feedback, examining its subjects and reasons for its consolidation. Emphasizing the chronicled, social, and scholarly foundation that contributed to the rise and advancement of women's activist scholarly feedback as a Western basic development. Combining hypothetical systems with down to earth application, scholarly settings with social activism, may be a key characteristic of women's activist belief system. In other words, composing, inventiveness, and feedback are not fair individual, subjective endeavors, but are instep a political activity an exertion centered on accomplishing social alter.